PERBANDINGAN PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI NOMOR 62/PID.SUS-TPK/2016/PN.PBR DENGAN PUTUSAN NOMOR 2233 K/PID.SUS/2017 TERKAIT TINDAK PIDANA SUAP - Bijaksono, Athfal Habiby; Effendi, Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corruption is one form of crime that damages national discipline. Things that are done insociety and society do not go well, causing financial impacts and decreasing national morale. Thepractice of corruption spreads in several State institutions such as the executive, legislative, andjudiciary both central and regional. The act of criminal offenses is one of the impacts on the socialand economic rights of the community. One of the Singer Corruption Crime cases because bribeAPBD-P 2014 dan RAPBD 2015 Interesting Singer Decision for review was reviewed there was adisparity in decision betwen defendant I and defendant II, because in the First Court the DefendantII was acquitted by the panel of judges. Then the public prosecutor at the Indonesian CorruptionEradication Commission filed a cassation law at the Supreme Court level, in which Tyris II wasfound guilty. The purpose of Singer Thesis Writing, namely: First, to review the basic basis of theJudge's consideration in dropping case decision number 62 / Pid.Sus-TPK / 2016 / PN.Pbr withCase Verdict Number 2233 K / Pid.Sus / 2017 defendant. second, to find out the power of proof inCase Number 2233 K / Pid.Sus / 2017 at the Supreme Court Cassation level.Operating Singer Research can be classified in the type of normative legal research,descriptive singer research is, that is, a research that describes operating clearly and in detailregarding the construction of judges' thinking in imposing criminal acts on corruption, data sourcesthat are used secondary data consisting of primary legal material , secondary legal materials, andtertiary legal materials, techniques for entering data in this study by studying the literature, after thedata collected is then analyzed to draw conclusions.From the results of research and discussion there are two things that can be concluded. First,Judex facti basic considerations using the way of Thinking Legism / Positivism and following anarrow meaning about the notion of Corruption Crime and tends to prioritize Judge Beliefs withoutconsidering evidence according to Article 184 paragraph (1) of the Criminal Procedure Code. Therationale of the cassation law on Judex Juris, the judge put forward on the spirit of progressive lawnamely juridical, philosophical and sociological decisions, the creator of a sense of justice andexpediency. Second, the strength of evidence in the cassation level is the dimensions of courtdecisions based on the theory of coherence or consistency, namely the truth that proves one thingthat is related to Article 184 of the Criminal Procedure Code. In Article 188 of the CriminalProcedure Code the application of the applicable provisions to determine its provisions.Keywords: Corruption Crime - Judge Decision - Proof